PENGEMBANGAN DESA WISATA BERBASIS KEARIFAN LOKAL GUNA MENINGKATKAN PENDAPATAN MASYARAKAT DALAM PERSPEKTIF EKONOMI HINDU DI DESA ADAT DUKUH PENABAN - I Kadek Widiantana; A.A. Diah Indrayani (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
The Traditional Village of Dukuh Penaban Karangasem develops a tourism village based on local wisdom, by utilizing the palm tree heritage owned by the local community. With the palm tree heritage owned by the community, a museum called the Pustaka Lontar Dukuh Penaban Museum was able to be built. The Pustaka Lontar Dukuh Penaban Museum has received various awards. The development of this tourist village is expected to be one of the models for developing a tourism village based on local wisdom. Therefore, it is necessary to conduct an in-depth investigation related to the model of developing the tourist village, so that it can be an example in the development of tourist villages in other places. The method used in this research is qualitative with a case study approach. The Lontar Pustaka Museum in Dukuh Penaban is a model of a lontar museum with a lively lontar cultural ecosystem that is different from other lontar storage places. The living lontar cultural ecosystem has meaning, everything related to lontar can be found in the Museum, from the process of making the lontar material, to the application of the contents of the lontar. this can be a special attraction and ultimately have a positive impact on the welfare of the community in the village.